Implementasi Strategi Bauran Pemasaran dalam Meningkatkan Volume Penjualan Ekspor Pada PT Panjimas Textile - Mia Dwi Risandi; Jojok Dwiridotjahjono (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
There are many strategies that can be used to increase sales volume and attract customers. Marketing generally focuses on products, pricing, distribution policies, and also how to promote. The purpose of this study is to determine the marketing strategy that can increase sales volume at PT Panjimas Textile in Gresik city. This type of research is descriptive research. The research method used is through interviews, documents, and observation results. The subject of this research is the export marketing division employee staff at PT Panjimas Textile. The object of this research is PT Panjimas Textile. The results showed that the strategy used by PT Panjimas Textile is to implement the marketing mix or marketing 4p which includes Product, Price, Place, Promotion to increase export sales volume. The conclusion of this study is that the strategy used is the application of the 4p marketing mix successful in increasing the volume of export sales at PT Panjimas Textile.